Tocilizumab in refractory rheumatoid arthritis: long-term efficacy, safety, and tolerability beyond 2 years - Farah Z (Dove Medical Press, 2016)
Ziad Farah, Sabreen Ali, Fiona Price-Kuehne, Charles G Mackworth-Young Department of Rheumatology, Charing Cross Hospital, London, UKObjectives: To evaluate the long-term efficacy and safety of tocilizumab (TCZ) in clinical patients with rheumatoid arthritis (RA) refractory to synthetic disease-modifying antirheumatic drugs, anti-tumor necrosis factor agents, and B-cell depletion therapy with rituximab (RTX).Methods: We conducted a single-center retrospective study of 22 patients with RA treated with TCZ. We collected data including demographics and medication histories. We recorded clinical parameters including tender joint counts and swollen joint counts, and laboratory parameters including inflammatory makers and lipid profiles over regular intervals of TCZ treatment.Results: In all, 22 patients with RA were included, 20 of whom were female. The median age at the first dose of TCZ was 62 years (range: 35–75 years). The mean duration of the disease from diagnosis with RA to May 2015 was 15.7 years (range: 6–30 years). A total of 15 out of 22 patients remained on TCZ at the end of the study, and in all, there was an improvement in markers of disease activity following initiating TCZ. The effect was sustained for a mean of 35 months (SD ±15.5 months, range: 9–72 months). Of the 17 patients who failed to respond to RTX previously, 12 patients remained on TCZ. In all, eight out of 22 patients developed adverse events, five of whom discontinued TCZ. In contrast to previously documented short-term data, TCZ did not result in a statistically significant (P<0.05) long-term deterioration in lipid profile for any of the lipid parameters measured in our cohort (mean ± SD at initiation of TCZ to most recent follow-up: total cholesterol 5.25±1.05 to 5.28±0.77 mmol/L, high-density lipoprotein 1.72±0.54 to 1.67±0.43 mmol/L, low-density lipoprotein 3.05±0.98 to 2.98±0.81 mmol/L, and cholesterol to high-density lipoprotein ratio 3.41±1.23 to 3.40±1.22).Conclusion: The efficacy of TCZ in patients with RA refractory to disease-modifying drugs, including anti-tumor necrosis factor blockade and RTX, is sustained over 3 years. TCZ confers a good safety profile in the long term even in patients who previously developed adverse events to other rheumatic drugs. In the long run, there is no statistically significant deterioration in lipid profile during treatment with TCZ.Keywords: tocilizumab, rheumatoid arthritis, refractory rheumatoid, long term, efficacy, safety, tolerability